The doctrine of wilful blindness in drug offences: Adili Chibuike Ejike v Public Prosecutor [2019] 2 SLR 254 - WHANG, Rennie (Institutional Knowledge at Singapore Management University, 2020)
In Adili Chibuike Ejike v Public Prosecutor [2019] 2 SLR 254, the Court of Appeal clarified the operation of the wilful blindness doctrine in the context of knowing possession for drug offences. In particular, it affirmed wilful blindness as a doctrine of substantive rather than evidential law, which applies as a limited extension to the legal requirement of actual knowledge. The court then articulated a three-part test for the finding of wilful blindness in relation to knowledge as an ingredient of possession. However, it left open the content of the doctrine as applied to the element of knowledge in drug offences. This note agrees with the characterisation of the doctrine, proposes a reformulation of the three-part test, and analyses the operation of the doctrine in rebutting the presumption of knowledge under s 18(2) of the Misuse of Drugs Act (Cap 185, 2008 Rev Ed).